Макромоделирование процессов энергообмена в системе "электропривод – сеть" на основе принципов декомпозиции и редукции - Заболотный, Анатолий Петрович (НТУ "ХПИ", 2010)
The paper describes an algorithm for optimization of energy exchange processes in the system of "Electric drive - Network" based on the principles of decomposition and reduction. The block - diagram of this algorithm is resulted.
Macromodelling of energy exchange processes in the system of "electric drive – network" based on the principles of decomposition and reduction
Keywords: электропривод частотно-регулируемый; электропривод асинхронный; моделирование математическое; метод подсхем